Prenatal Depression in Women in the Third Trimester: Prevalence, Predictive Factors, and Relationship With Maternal-Fetal Attachment - Zhang, Ling; Wang, Lei; Cui, Shu; Yuan, Qiuyu; Huang, Cui; Zhou, Xiaoqin (Frontiers in Public Health, 2021)
Objective: The prevalence of prenatal depression in pregnant women has found to be high, which may adversely affect the intimacy of a mother to her fetus. Few studies have investigated the relationship between prenatal depression and maternal-fetal attachment in pregnant Chinese women. This study is thus designed to evaluate the prevalence rate, predictive factors of prenatal depression in Chinese pregnant women in the third trimester of pregnancy, and the effect of prenatal depression on maternal-fetal attachment. Methods: A total of 340 pregnant women in the third trimester of pregnancy were recruited from a hospital in Anhui Province. The Edinburgh Postpartum Depression Scale (EPDS) was rated to assess the prenatal depression; the Pittsburgh Sleep Quality Index (PSQI) and Zung Self-Rating Anxiety Scale (SAS) were used to assess sleep quality and anxiety level for all participants. The Maternal Antenatal Attachment Scale (MAAS) was used to assess maternal-fetal attachment. Results: The prevalence of prenatal depression in the participants was high (19.1%) in our study. The scores of prenatal anxiety and sleep disorders were higher with prenatal depression than in those without prenatal depression (47.6±9.5 vs 38.9±6.9; 8.3±3.3 vs 6.1±2.7, all p < 0.01). MAAS quality was lower in prenatal depression women than those in non-prenatal depression women (43.8±5.6 vs 46.4±4.5, p < 0.01). Correlation analysis showed that prenatal depression was associated with parity, prenatal education, education level, marital satisfaction, anxiety and sleep disorders (all p<0.05). Furthermore, binary logistic regression results showed that anxiety and sleep disorders were risk factors for prenatal depression. Prenatal education, higher marriage satisfaction were protective factors for prenatal depression. In addition, correlation analysis also showed that prenatal depression was positively correlated with MAAS intensity, but negatively correlated with MAAS quality. Conclusions: Our results indicated a high prevalence of prenatal depression in women in the third trimester. Prenatal education and higher marital satisfaction were protective factors for prenatal depression; antenatal anxiety and sleep disorders during pregnancy were risk factors for prenatal depression. Prenatal depression was negatively correlated with MAAS quality, but positively correlated with MAAS intensity.